Majorization Relation in Quantum Critical Systems - 淮琳萍 张煜然 刘思远 杨文力 屈世显 范桁 (Chinese physics letters, 2014)
The most basic local conversion is local operations and classical communications （LOCC）, which is also the most natural restriction in quantum information processing. We investigate the conversions between the ground states in quantum critical systems via LOCC and propose a novel method to reveal the different convertibilities via majorization relation when a quantum phase transition occurs. The ground-state local convertibility in the one-dimensional transverse field Ising model is studied. It is shown that the LOCC convertibility changes nearly at the phase transition point. The relation between the order of quantum phase transitions and the LOCC convertibility is discussed. Our results are compared with the corresponding results by using the Renyi entropy and the LOCC convertibility with assisted entanglement.